Mid-term safe and effective profile of the Magmaris scaffold in percutaneous coronary intervention: a prospective, single-center study - Truong, Binh Quang; Tran, Hoa; Nguyen, Vinh Xuan; Nguyen, Chinh Duc; Nguyen, Khang Duong; Vu, Vu Hoang (Frontiers in Cardiovascular Medicine, 2023)
Introduction Significant advances have been made in the diagnosis and treatment of coronary artery disease over the years. New generations of scaffolds containing novel material and eluting drug have produced one of the most significant advancements in coronary intervention. The newest generation would be Magmaris with a magnesium frame and a sirolimus cover. Methods From July 2018 to August 2020, 58 patients treated with Magmaris at the University Medical Center Ho Chi Minh City were enrolled in this study. Results A total of 60 lesions were stented, 60.3% of which were left anterior descending (LAD) lesions. There was no in-hospital event. Within 1 year after discharge, we noted one myocardial infarction event that required target-lesion revascularization, one stroke event, one non-target-lesion revascularization patient, two target-vessel revascularization patients, and one in-stent thrombosis. Among them, one myocardial infarction occurrence, one non-target-lesion revascularization, and one in-stent thrombosis event were recorded within the first 30 days after discharge. Conclusion In conclusion, the Magmaris scaffold is a safe and effective option for structural procedures performed with imaging device support, particularly intravascular ultrasound.